Posttranscriptional and Posttranslational Regulation of Actin. Issue 12 (19th November 2018) - Rodriguez, Alexis; Kashina, Anna
ABSTRACT: Actin is one of the most abundant intracellular proteins, essential in every eukaryotic cell type. Actin plays key roles in tissue morphogenesis, cell adhesion, muscle contraction, and developmental reprogramming. Most actin studies have focused on its regulation at the protein level, either directly or through differential interactions with over a hundred intracellular binding partners. However, numerous studies emerging in recent years demonstrate specific types of nucleotide‐level regulation that strongly affect non‐muscle actins during cell migration and adhesion and are potentially applicable to other members of the actin family. This regulation involves zipcode‐mediated actin mRNA targeting to the cell periphery, proposed to mediate local synthesis of actin at the cell leading edge, as well as the recently discovered N‐terminal arginylation that specifically targets non‐muscle β‐actin via a nucleotide‐dependent mechanism. Moreover, a study published this year suggests that actin's essential roles at the organismal level may be entirely nucleotide‐dependent. This review summarizes the emerging data on actin's nucleotide‐level regulation. Anat Rec, 301:1991–1998, 2018. © 2018 Wiley Periodicals, Inc.